Market structure, state ownership and monetary policy transmission through bank lending channel: Evidence from Vietnamese commercial banks - Nguyen, Huu Huan; Ngo, Minh Vu; Nguyen, Thanh Phuc (Economics and Business Letters, 2021)
This paper examines the impact of market structure and state ownership on bank lending as a transmission channel for monetary policies. For controlling the effects of bank heterogeneities and macroeconomic factors on bank lending, dynamic models using two-step difference GMM with panel data collected from 25 Vietnamese commercial banks and the Vietnamese banking sector from 1999 to 2017 are employed. Results indicate that a higher level of concentration in the banking market and state ownership dampen the expected impacts of interbank interest rate on the loan growth in commercial banks, which decreases the effectiveness of monetary policy via the bank lending channel. These results are robust regarding the use of alternative measures of market structure and the inclusion of event time variables in the dynamic model. Based on the findings, monetary policy could be implied using the significant moderating impacts of state-ownership as well as the market structure of the Vietnamese banking sector on the relationship between bank loan supply and interbank interest rate.